2009
DOI: 10.1007/s00431-009-0968-2
|View full text |Cite
|
Sign up to set email alerts
|

A prospective 7-year survey on central venous catheter-related complications at a single pediatric hospital

Abstract: The aims of this study were to assess the incidence and risk factors of major central venous catheter (CVC)-related complications in a large cohort of children affected by oncological, hematological, or immunological diseases in a 7-year prospective observational study at a single center. Nine hundred fifteen CVCs were inserted in 748 children for a total period of 307,846 CVC-days. Overall, 298 complications were documented with a complication rate of 0.97/1,000 CVC-days: 105 mechanical complications (disloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
11
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 37 publications
(53 reference statements)
5
62
11
3
Order By: Relevance
“…These data also were not included in the review. We were unable to ascertain the number of catheter days in 23 studies, [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]84,85,92,97,99,122 which excluded their data from contributing to the meta-analysis reporting failure and complications per 1000 catheter days. Because of a lack of data, the rate of CVAD failure per 1000 catheter days for nontunneled, percutaneous CVADs could not be estimated.…”
Section: Study Qualitiesmentioning
confidence: 99%
“…These data also were not included in the review. We were unable to ascertain the number of catheter days in 23 studies, [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]84,85,92,97,99,122 which excluded their data from contributing to the meta-analysis reporting failure and complications per 1000 catheter days. Because of a lack of data, the rate of CVAD failure per 1000 catheter days for nontunneled, percutaneous CVADs could not be estimated.…”
Section: Study Qualitiesmentioning
confidence: 99%
“…In a retrospective review of pediatric cancer patients with CVCs at another medical institution in Taiwan between 2001 and 2005, 13 out of 228 (5.7%) catheters were removed for CRBSI [8]. This indicates that the management of CRBSI in children with cancer in Taiwan after 2000 is similar to that in other developed countries [1,[5][6][7].…”
Section: Discussionmentioning
confidence: 98%
“…Although young age was not a risk factor for CRBSI in children with cancer, it was a risk factor for tunnel infections [5]. It is reported that 5-9% of CVCs had to be removed because of CRBSI in pediatric cancer patients [1,[5][6][7][8]. A recent study showed that 87% of CRBSI episodes were successfully treated with antibiotic therapy and without catheter removal in children with cancer [9].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…17,29,[34][35][36][37][38][39][40][41] A taxa de infeção é mais alta em recém-nascidos e no caso de cateteres de múltiplo lúmen. A incidência de complicações infeciosas é substancialmente maior na NP, quer seja por PICC quer seja por CVC, com taxas até seis vezes superiores na síndroma de intestino curto devido à translocação bacteriana.…”
unclassified